DOI: 10.17760/d20265269
|View full text |Cite
|
Sign up to set email alerts
|

Persisting past probation : an exploration of the experiences and the perceptions of community college students on academic probation, an interpretative phenomenological analysis

Abstract: The first year, first-semester community college students on academic probation and the factors affecting their academic success have been on the rise. As such, many students who are not making satisfactory academic progress (SAP) are at risk of losing their financial aid and, quite possibly, dropping out of school. The purpose of this study was to investigate how community college students who experience academic probation in their first year make sense/meaning of that experience and transition to become succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…For example, Barry (2015) documented the positive influence of students' relationships with their families and with the instructors of the course in a study of 14 students on probation. In a study of eight students at a community college, Erazo (2017) found that the students had limited information before college, lacked “emotional maturity and academic discipline” (p. 103), failed to understand college expectations and how to access resources, and neglected to develop relationships with faculty and staff. These students became successful when they realized how college differed from high school, and when they began participating in extracurricular activities such as clubs and interest groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Barry (2015) documented the positive influence of students' relationships with their families and with the instructors of the course in a study of 14 students on probation. In a study of eight students at a community college, Erazo (2017) found that the students had limited information before college, lacked “emotional maturity and academic discipline” (p. 103), failed to understand college expectations and how to access resources, and neglected to develop relationships with faculty and staff. These students became successful when they realized how college differed from high school, and when they began participating in extracurricular activities such as clubs and interest groups.…”
Section: Introductionmentioning
confidence: 99%
“…Third, students with a weak sense of belonging felt even more alienated when they were on probation. All three studies (Barry, 2015; Blaney, 2014; Erazo, 2017) emphasized that none of their informants attributed their academic difficulties to inadequate academic preparation.…”
Section: Introductionmentioning
confidence: 99%